REFRAMING SUFISM AS A FRAMEWORK FOR RELIGIOUS MODERATION: Negotiating Islamic Authority and Social Cohesion in the Indonesian Majelis Pengkajian Tauhid Tasawuf (MPTT-I) - Muhammad Riza; Ridwan Nurdin; Ibnu Qodir; Dicky Wirianto; Mardianto Mardianto (State Islamic University North Sumatra, 2026)
While religious moderation has become a central discourse in Indonesia’s pluralistic society, existing studies have largely examined it through legal-political and institutional frameworks, leaving its spiritual-ethical dimension, particularly the role of Sufism (tasawuf), insufficiently explored. This study addresses this gap by examining how Sufi traditions serve as a conceptual and practical resource for constructing religious moderation at the grassroots level. Using a qualitative case study of the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTT-I) congregation in Aceh, this research employed purposive and snowball sampling to gather data from key informants, including Abuya Amran Wali Al-Khalidi, district leaders (wali nanggroe), and MPTT-I members. The data were analyzed using Miles and Huberman’s interactive model, consisting of data collection, condensation, display, and conclusion drawing. The findings show that MPTT-I integrates three major Sufi traditions, namely falsafi, sunni, and akhlaqi, into its spiritual teachings. These traditions form a moral-spiritual framework that nurtures religious moderation through values such as balance (tawâzun), acceptance of diversity, self-restraint, tolerance, compassion, and communal harmony. This study contributes by proposing a Sufism-based model of religious moderation, showing that moderation emerges not only from policy or doctrine but also from embodied spiritual practice.